2012
DOI: 10.1271/bbb.120782
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Plant Genes for Arbuscular Mycorrhiza-Inducible Phosphate Transporters and Fungal Vesicle Formation in Sorghum, Barley, and Wheat Roots

Abstract: Sorghum shows strong growth stimulation on arbuscular mycorrhizal (AM) symbiosis, while barley and wheat show growth depression. We identified the AM-inducible phosphate transporter genes of these cereals. Their protein products play major roles in phosphate absorption from arbuscules, intracellular fungal structures. Unexpectedly, barley and wheat expressed the AM-inducible genes at high levels. Hence the cause of their growth depression appears to be unrelated to the transcription of these genes. Notably, fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 27 publications
1
21
0
2
Order By: Relevance
“…The Gene ID TRIAE_CS42_4BL_TGACv1_320302_AA1034400 matched with TaPHT1.2-4B and TaPHT1.9-4B ; and no Gene ID was found to match with TaPHT1.1-4B and TaPHT1.10-U cloned in the current study or TaPHT1.11-4B (former name TRIae; Pht1;11 ) cloned by Sisaphaithong et al (2012). Therefore, we identified a total of 36 TaPHT1 genes (Supplementary Table S3).…”
Section: Resultsmentioning
confidence: 84%
See 3 more Smart Citations
“…The Gene ID TRIAE_CS42_4BL_TGACv1_320302_AA1034400 matched with TaPHT1.2-4B and TaPHT1.9-4B ; and no Gene ID was found to match with TaPHT1.1-4B and TaPHT1.10-U cloned in the current study or TaPHT1.11-4B (former name TRIae; Pht1;11 ) cloned by Sisaphaithong et al (2012). Therefore, we identified a total of 36 TaPHT1 genes (Supplementary Table S3).…”
Section: Resultsmentioning
confidence: 84%
“…TaPHT1.5 in Branch IV and TaPHT1.7 in Branch III were expressed at very low levels in both of the hydroponic culture and field experiment ( Figures 3C, 4C ). The reported AM fungi inducible PHT1 s were grouped into Branch VI ( Figure 1 ), including TaPHT1.8 and TaPHT1.11 from wheat, HvPHT1.8 and HvPHT1.11 from barley, ZmPHT1.6 from maize (Glassop et al, 2005; Sisaphaithong et al, 2012), and OsPHT1.11 from rice (Paszkowski et al, 2002). Here, we found that TaPHT1.8 was upregulated by low P treatment in the field experiments ( Figures 4C, 6D ), but not by low P treatment in the hydroponic culture ( Figure 3C ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Rice is also a suitable material for investigating the molecular mechanisms of symbiosis with arbuscular mycorrhizal (AM) fungi, which colonize the roots of most land plant species [5][6][7][8][9]. However, the number of reports describing the growth response of rice plants to AM fungi is unexpectedly much smaller than those of other crops such as maize, sorghum, legumes, and vegetables [10,11]. The reason may be that rice plants are grown mainly in anoxic paddy fields, in which the presence of AM fungi is still a matter of debate [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%